Pembiasaan Shalat Dhuha Dalam Pembentukan Karakter Mandiri Beribadah Siswa Kelas III MI Muhammadiyah PK Kartasura Tahun Ajaran 2016/2017 - Rusady, Novitasari Putri; , Nur Amalia S.S., M.Teach (2017)
This study aims to determine (1) Habituation Duha prayer held at MI Muhammadiyah PK Kartasura. (2) Independence of worship through Duha prayer in class III MI Muhammadiyah PK Kartasura. (3) Independence of Duha prayer worship third grade students of MI Mihammadiyah PK Kartasura when school holidays at home. This study is a qualitative research with phenomenological research type. Collecting data in this study is by interview, observation and documentation. The research instrument used observation and interview sheet. Activities in the data analysis: data reduction, data presentation, and conclusion. Test the validity of the data using triangulation techniques and resources. The results showed that: (1) Habituation Duha prayer in MI Mihammadiyah PK Kartasura: a) Habituation Duha prayer done at the first break time (09: 30-10: 00 pm). b) There is Duha prayer worshipers schedule for each class. c) Habituation done Duha prayer in congregation. d) students freed in eimplementation of Duha prayer outside of the specified chedule.e)abituation Duha prayer done two cycles. f) Habituation is coordinated by the responsible Duha prayer Duha prayer. g) The students of class III is less serious and responsible when Duha prayer in congregation. h) There is a punishment for students who are not accustom Duha prayer .; (2) Grade III has not shown independence in Duha prayer worship .; (3) Students are familiar with the Duha prayer set by the school, but not independent when the school holidays at home.